2012
DOI: 10.1152/physrev.00009.2012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Physiology of SPAK and OSR1: Two Ste20-Related Protein Kinases Regulating Ion Transport

Abstract: SPAK (Ste20-related proline alanine rich kinase) and OSR1 (oxidative stress responsive kinase) are members of the germinal center kinase VI sub-family of the mammalian Ste20 (Sterile20)-related protein kinase family. Although there are 30 enzymes in this protein kinase family, their conservation across the fungi, plant and animal kingdom confirms their evolutionary importance. Already, a large volume of work has accumulated on the tissue distribution, binding partners, signaling cascades, and physiological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 338 publications
(536 reference statements)
1
108
0
Order By: Relevance
“…The proline/alanine-rich region of SPAK is of interest as it constitutes the differentiating feature from its ancestor kinase OSR1 (2). As demonstrated by our study, this unique region is primarily targeted by the protease, suggesting it may be involved in regulating the kinase.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The proline/alanine-rich region of SPAK is of interest as it constitutes the differentiating feature from its ancestor kinase OSR1 (2). As demonstrated by our study, this unique region is primarily targeted by the protease, suggesting it may be involved in regulating the kinase.…”
Section: Discussionmentioning
confidence: 64%
“…In recent years a kinase cascade involving the Ste20p-like kinases, SPAK 2 (STK39) and OSR1 (OxSR1), has emerged as an important regulator of salt transport in the kidney (1,2). The kinases regulate two transport mechanisms involved in Na ϩ reabsorption: the Na-K-2Cl cotransporter, NKCC2, expressed in the thick ascending limb of Henle (TAL), and the Na-Cl cotransporter, NCC, expressed in the distal convoluted tubule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular reconstitution studies and mouse genetics demonstrated the importance of WNK function in cell volume regulation and maintenance of blood pressure (13-19). Control of cation-chloride cotransporters through OSR1 and SPAK is among the best-documented actions of WNKs in diverse tissues (5,(20)(21)(22).WNKs also regulate serum-and glucocorticoid-inducible protein kinases (SGKs) through a noncatalytic mechanism leading to increased sodium influx through the epithelial sodium channel (ENaC) (23, 24). SGKs and the related Akt enzymes are activated by phosphorylation on multiple sites, most prominently a residue in the activation loop by the phosphoinositide-dependent protein kinase and on a second site in a C-terminal hydrophobic motif (25).…”
mentioning
confidence: 99%
“…Cellular reconstitution studies and mouse genetics demonstrated the importance of WNK function in cell volume regulation and maintenance of blood pressure (13)(14)(15)(16)(17)(18)(19). Control of cation-chloride cotransporters through OSR1 and SPAK is among the best-documented actions of WNKs in diverse tissues (5,(20)(21)(22).…”
mentioning
confidence: 99%